Immune Checkpoint Inhibitor Therapy for Prostate Cancer: Present and Future Prospectives - Vikrant Rai (Biomolecules)
Prostate cancer, a slow-growing tumor, develops through the over-proliferation of malignant cells in the prostate and is one of the most common types of cancer. Active surveillance, radical prostatectomy, external beam radiation, brachytherapy, cryotherapy, stereotactic body radiation therapy, hormone therapy, and chemotherapy are common treatment strategies for prostate cancer. However, resistance to treatment in advanced prostate cancer is a concerning issue in the use of these therapies. Immune checkpoint inhibitor (ICI) therapy for prostate cancer is an emerging strategy for the treatment of advanced prostate cancers but the resistance and limited efficacy to ICIs observed in metastatic castration-resistant prostate cancer (mCRPC) raises concerns. The ongoing clinical trials for combination therapies for mCRPC have provided some hope. This review concisely discusses the molecular and cellular mechanisms, immunotherapy, the limitations of ICIs, combination therapies, and the prospects of developing novel therapeutics for prostate cancer.